2012
DOI: 10.1091/mbc.e12-04-0299
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar accumulation of APE1 depends on charged lysine residues that undergo acetylation upon genotoxic stress and modulate its BER activity in cells

Abstract: The functional importance of APE1 nucleolar accumulation is described. It is shown that acetylation of Lys27–35, affecting local conformation, regulates APE1 function by 1) controlling its interaction with NPM1 and rRNA and its nucleolar accumulation, 2) modulating K6/K7 acetylation status, and 3) promoting APE1 BER activity in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
152
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(165 citation statements)
references
References 62 publications
10
152
2
1
Order By: Relevance
“…Furthermore, they reported that SIRT1 activity mediated the increased association of APE1 with XRCC1, a key BER scaffolding enzyme, in response to MMS treatment, and that depletion of SIRT1 resulted in sensitivity of HeLa cells to MMS and increased AP-site accumulation, both of which could be rescued by overexpression of APE1 (Yamamori et al 2010). However, subsequent work found that SIRT1 interacted with APE1 K4pleR but not with the acetylation-mimicking APE1 K4pleA mutant that is released from the nucleolus by NPM1 upon induction of genotoxic stress, and failed to deacetylate APE1 K4pleA at K6/K7, despite the fact that this form possesses greater AP-endonuclease activity than either APE1 WT or APE1 K4pleR (Lirussi et al 2012). …”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, they reported that SIRT1 activity mediated the increased association of APE1 with XRCC1, a key BER scaffolding enzyme, in response to MMS treatment, and that depletion of SIRT1 resulted in sensitivity of HeLa cells to MMS and increased AP-site accumulation, both of which could be rescued by overexpression of APE1 (Yamamori et al 2010). However, subsequent work found that SIRT1 interacted with APE1 K4pleR but not with the acetylation-mimicking APE1 K4pleA mutant that is released from the nucleolus by NPM1 upon induction of genotoxic stress, and failed to deacetylate APE1 K4pleA at K6/K7, despite the fact that this form possesses greater AP-endonuclease activity than either APE1 WT or APE1 K4pleR (Lirussi et al 2012). …”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 98%
“…This interaction, mediated by binding of the lysine-rich APE1 N-terminal tail to NPM1's N-terminal region containing the oligomerization domain and acidic tracts, results in the robust recruitment of APE1 into nucleoli (Fantini et al 2010;Vascotto et al 2009). Upon induction of genotoxic stress such as base D r a f t 23 oxidation or methylation, lysines within the APE1 N-terminal become acetylated, interrupting the NPM1-APE1 interactions and inducing translocation of APE1 from the nucleolus to the nucleoplasm (Fantini et al 2010;Lirussi et al 2012). Mutation of four of these residues (K27, K31, K32, K35) to acetylation-mimicking uncharged alanines (termed APE1 K4pleA ) results in constitutive translocation of APE1 to the nucleoplasm, while inhibition of acetylation by lysine-to-arginine mutations (APE1 K4pleR ) constitutively prevents translocation; these same mutations inhibit (APE1 K4pleA ) or enhance (APE1 K4pleR ) the interaction of APE1 with NPM1, emphasizing the importance of this interaction to the regulation of APE1's nucleolar sequestration (Lirussi et al 2012).…”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 99%
See 3 more Smart Citations